Diagnoses and trends in use of imaging for low back pain in four Australian emergency departments between 2012 and 2019. (30th January 2022) - Blokzijl, Johan; Lee, Hopin; Cullen, Louise; Coggins, Andrew; Golding, Michael; Gillett, Mark; Middleton, Paul M; Ferreira, Giovanni E; Machado, Gustavo C; Maher, Christopher G; Traeger, Adrian C
Abstract: Objective: We aimed to determine, in those who present to the ED with low back pain (LBP): (i) the prevalence of four key diagnostic categories, (ii) trends in lumbar imaging from 2015 to 2019 and (iii) the effect of a new model of care on lumbar imaging in the ED. Methods: We conducted a retrospective analysis of routinely collected medical data of four tertiary hospitals in Sydney, Australia. We analysed ED presentations for LBP between January 2012 and October 2019. Outcomes were the prevalence of four key diagnostic categories of LBP and use of lumbar imaging. We examined trends in lumbar imaging over time and used interrupted time series analysis to determine the impact of model of care implementation on imaging use. Results: There were 31 168 presentations for LBP of which 64.5% were non‐specific LBP, 27.2% were problems beyond the spine, 5.3% were LBP with neurological signs and 2.3% were serious spinal conditions. 28.9% received lumbar imaging; use did not change substantially between 2012 and 2019. Patients diagnosed with serious spinal conditions were more likely to receive imaging (59%) than those diagnosed with non‐specific LBP (29%). Implementation of a state‐wide model of care in November 2016 did not appear to influence imaging use. Conclusion: Most presentations to the ED for LBP are for non‐specific LBP. Around 2% will have specific spinal pathology. Use of imaging in those diagnosed with non‐specific LBP remains high and was unaffected by implementation of a state‐wide model of care. Abstract : We aimed to determine, in those who present to the ED with low back pain (LBP): (i) the prevalence of four key diagnostic categories, (ii) trends in lumbar imaging from 2015 to 2019 and (iii) the effect of a new model of care on lumbar imaging in the ED. Around 2% of people have specific spinal pathology. People diagnosed with serious spinal conditions were more likely to receive imaging (59%) than those diagnosed with non‐specific LBP (29%). Implementation of a state‐wide model of care in November 2016 did not appear to influence imaging use in non‐specific LBP.